Analysis and Modulation of In Vitro Cell Response to Metal Ions From CoCrMo Alloys Used in Orthopaedic Applications - Baskey, Stephen James (Université d'Ottawa / University of Ottawa, 2015)
Despite the high success rates of hip replacements, implant-wear mediated periprosthetic osteolysis remains the most prominent cause of long-term implant failure. Other adverse tissue reactions including hypersensitivity reactions and pseudotumors have also recently been reported as a cause for short-term implant failures. The objectives of this thesis were: 1.) To analyze the effects of Co2+ and Cr3+ released from CoCrMo alloys used in hip implants on macrophage chemokine release; 2.) To determine if Co2+, Cr3+, and the chemokines in cultures of macrophages exposed to Co2+ and Cr3+ can induce migration of T and B lymphocytes; and 3) To analyze the potential modulation of macrophage response to Cr3+ using simvastatin as an anti-inflammatory agent. Results showed that the release of TNF–α and CC chemokines were ion-specific and dose-dependent. Results also suggested that Co2+ and Cr3+ may be capable of directly stimulating the migration of T cells, but not that of B cells, suggesting the potential of these ions to create a micro-environment that would favour a T cell-mediated response in vivo. Results also showed that simvastatin was capable of decreasing chemokine release in macrophages exposed to Cr3+, suggesting its potential to modulate the Cr3+-induced inflammatory response. Together, these studies improve the understanding of the role metal ions play in ion-mediated adverse tissue reactions and potential therapies that may modulate the immune response to metal ions.
Keywords: Orthopaedics; Hip Implants; CoCrMo alloys; Metal ions; Immune response; Macrophages; Lymphocytes; Therapeutic modulation; Simvastatin